PERAN FOLLOWERSHIP DALAM PENINGKATAN KECERDASAN EKOLOGIS SANTRI DI PESANTREN EKOLOGI MISYKAT AL-ANWAR - Sepudin, Mohammad Fahmi; Asy'ari, Hasyim; Musfah, Jejen (Smart Education, 2025)
Abstract: This study aims to analyze the role of followership in achieving an increase in the ecological intelligence of students at Misykat Al Anwar Ecological Boarding School. This approach uses a qualitative approach with an ecological psychology paradigm that focuses on human behavior towards their environment. Data collection was carried out by means of participatory observation, interviews, and documentation. The research findings show that teachers and education personnel mostly hold the values of social-ecological justice, thus becoming effective followers in realizing the goals of the institution. The big vision of the pesantren is to mainstream values, tolerance, justice and equality for marginalized civil society groups and advance the struggle for environmental justice for the future of life. The results revealed that Misykat Al Anwar Ecological Boarding School succeeded in increasing ecological intelligence through three main programs, namely the Green Curriculum, Organic Food Ecosystem, and Waste Management. The success of the program is supported by the role of followership from various parties, including caregivers, teachers, and education personnel. All parties show high active involvement, but most followers have moderate to low critical thinking scores. This is a challenge in encouraging more innovative contributions to the pesantren's vision and mission in improving ecological intelligence.. Keywords: Ecological Intelligence, Followership, Ecological Pesantren Abstrak: Penelitian ini bertujuan untuk menganalisis peran followership dalam mencapai peningkatan kecerdasan ekologis santri di Pesantren Ekologi Misykat Al Anwar. Pendekatan ini menggunakan pendekatan kualitatif dengan paradigma psikologi ekologis yang memfokuskan perilaku manusia terhadap lingkungannya. Pengumpulan data dilakukan dengan cara observasi partisipatif, wawancara, dan dokumentasi. Temuan penelitian menunjukan bahwa pengajar dan tenaga kependidikan sebagian besar memegang nilai-nilai keadilan sosial-ekologis, sehingga menjadi followers yang efektif dalam mewujudkan tujuan lembaga. Visi besar pesantren adalah mengarusutamakan nilai-nilai, toleransi, keadilan dan kesetaraan bagi kelompok masyarakat sipil marjinal serta memajukan perjuangan keadilan lingkungan untuk masa depan kehidupan. Hasil penelitian mengungkapkan Pesantren Ekologi Misykat Al Anwar berhasil meningkatkan kecerdasan ekologis melalui tiga program utama, yaitu Kurikulum Hijau, Ekosistem Pangan Organik, dan Tata Kelola Sampah. Keberhasilan program ditunjang oleh peran followership dari berbagai pihak, termasuk pengasuh, pengajar, dan tenaga pendidikan. Seluruh pihak menunjukkan keterlibatan aktif yang tinggi, namun sebagian besar pengikut memiliki skor berpikir kritis yang sedang hingga rendah. Hal ini menjadi tantangan dalam mendorong kontribusi yang lebih inovatif terhadap visi misi pesantren dalam meningkatkan kecerdasan ekologis. Kata kunci: Kecerdasan Ekologis, Followership, Pesantren Ekologi